A Co-based single-molecule magnet confined in a barium phosphate apatite matrix with a high energy barrier for magnetization relaxation. Issue 39 (28th April 2017) - Kazin, Pavel E.; Zykin, Mikhail A.; Trusov, Lev A.; Eliseev, Artem A.; Magdysyuk, Oxana V.; Dinnebier, Robert E.; Kremer, Reinhard K.; Felser, Claudia; Jansen, Martin
Abstract : A Co-ion introduced into the trigonal channel of an apatite-type lattice forms a magnetically anisotropic two-coordinated Co-complex with a record-high spin-reversal energy barrier. Abstract : An apatite-type barium phosphate with a high content of cobalt ions in the trigonal channels features slow relaxation of magnetization with an energy barrier U eff of up to 387 cm −1, which is well above the values for all so far known d-metal based single-molecule magnets (SMMs).